Glycosyl Hydrolase Genes and Enzymes of Neurospora crassa - Alan Radford (Fungal Genetics Reports, 2006)
An analysis of the genome of Neurospora crassa has identified genes encoding 84 putative glycosyl hydrolases, representing 24 different families in Henrissat's classification. Functionally, they include enzymes for the degradation of all major polysaccharides (including cellulase, hemicellulase, chitinase and pectinase).There is evidence of high levels of gene amplification, despite the presence of RIP, as there are eight representatives of family 3 (beta-glucosidases and xylosidases), five of family 7 (endo- and exo-glucanases), six of family 13 (amylases and maltase), nine of family 18 (chitinase), eight of family 47 (ER alpha-mannosidases), eleven of family 61 (endoglucanases) and seven of family 76 (alpha-mannanases).